In the Absence of Trading in Influence in Anti-corruption Laws: Legal Framework within the United Nations Convention against Corruption - Jupriyadi Jupriyadi; Imroatul Hasanah (Lex Publica, 2023)
Corruption poses an enduring global challenge, impacting countries across different developmental stages. This research aims to investigate the imperative need for the criminalization of trading in influence in Indonesia, with a particular focus on its alignment with the United Nations Convention Against Corruption (UNCAC). Indonesia’s ratification of the UNCAC in 2006 signifies a commitment to integrating its essential principles into domestic law to effectively combat corruption. While UNCAC Article 18 explicitly deals with trading in influence and recognizes it as a serious form of corruption, Indonesia has not yet incorporated it into its legal framework. Utilizing normative methods and drawing on secondary data sources such as legal documents and pertinent literature, this study underscores the urgency of incorporating criminal penalties for trading in influence into Indonesia’s anti-corruption law The research scrutinizes the harmonization of national interests with UNCAC obligations, examines the societal repercussions of this corrupt practice, evaluates the cost-effectiveness of criminalization, and appraises the state’s capacity for enforcement. By enacting laws against trading in influence, Indonesia can bolster its anti-corruption measures, extend its reach to a wider array of wrongdoers, and guarantee the application of legality and justice in addressing corruption-related cases. The theoretical implications revolve around aligning international anti-corruption norms with domestic legal systems, facilitating greater adherence to UNCAC principles in Indonesia, and providing valuable insights into the broader struggle against corruption globally. Keywords: Corruption, Trading in influence, UNCAC, Criminalization, Indonesia Abstrak. Korupsi menimbulkan tantangan global yang berkepanjangan, berdampak pada negara-negara di berbagai tahap pembangunan. Penelitian ini bertujuan untuk menyelidiki pentingnya kriminalisasi perdagangan pengaruh di Indonesia, dengan fokus khusus pada keselarasan dengan United Nations Convention Against Corruption (UNCAC). Ratifikasi UNCAC yang dilakukan Indonesia pada tahun 2006 menandakan komitmen untuk mengintegrasikan prinsip-prinsip penting UNCAC ke dalam undang-undang domestik untuk memerangi korupsi secara efektif. Meskipun Pasal 18 UNCAC secara eksplisit mengatur perdagangan pengaruh dan mengakuinya sebagai bentuk korupsi yang serius, Indonesia belum memasukkannya ke dalam kerangka hukumnya. Dengan menggunakan metode normatif dan memanfaatkan sumber data sekunder seperti dokumen hukum dan literatur terkait, penelitian ini menggarisbawahi pentingnya memasukkan hukuman pidana bagi perdagangan pengaruh ke dalam undang-undang antikorupsi di Indonesia. Penelitian ini mengkaji harmonisasi kepentingan nasional dengan kewajiban UNCAC, mengkaji dampak sosial dari praktik korupsi ini, mengevaluasi efektivitas biaya kriminalisasi, dan menilai kapasitas negara dalam penegakan hukum. Dengan memberlakukan undang-undang yang melarang perdagangan pengaruh, Indonesia dapat memperkuat langkah-langkah antikorupsinya, memperluas jangkauannya terhadap pelaku kejahatan yang lebih luas, dan menjamin penerapan legalitas dan keadilan dalam menangani kasus-kasus terkait korupsi. Implikasi teoretisnya berkisar pada penyelarasan norma-norma antikorupsi internasional dengan sistem hukum dalam negeri, memfasilitasi kepatuhan yang lebih besar terhadap prinsip-prinsip UNCAC di Indonesia, dan memberikan wawasan berharga mengenai perjuangan yang lebih luas melawan korupsi secara global. Kata kunci: Korupsi, Perdagangan pengaruh, UNCAC, Kriminalisasi, Indonesia